2019
DOI: 10.1088/1748-9326/ab4a6c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring trends in wet-season precipitation and drought indices in wet, humid and dry regions

Abstract: This study examines wet season droughts using eight products from the Frequent Rainfall Observations on GridS database. The study begins by evaluating wet season precipitation totals and wet day counts at seasonal and decadal time scales. While we find a high level of agreement among the products at a seasonal time scale, evaluations of 10 year variability indicate substantial non-stationary inter-product differences that make the assessment of low-frequency changes difficult, especially in data-sparse regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…For example, in R95p and R99p, MERRA2 has an increasing trend throughout the timeseries while CFSR appears to show a trend starting in about 2000. These trends are likely data artefacts as they are not present in any of the other products and could be responsible for the non-stationary systematic errors identified in Funk et al(2019) in this Focus Collection. These issues will be investigated further as part of the wider remit of the IPWG/GDAP/WCRP extreme precipitation project.…”
Section: Climatologymentioning
confidence: 93%
“…For example, in R95p and R99p, MERRA2 has an increasing trend throughout the timeseries while CFSR appears to show a trend starting in about 2000. These trends are likely data artefacts as they are not present in any of the other products and could be responsible for the non-stationary systematic errors identified in Funk et al(2019) in this Focus Collection. These issues will be investigated further as part of the wider remit of the IPWG/GDAP/WCRP extreme precipitation project.…”
Section: Climatologymentioning
confidence: 93%
“…It is widely reported that droughts and aridity will worsen under increasing greenhouse gas concentrations (Dai, 2013; Dai et al, 2018; Mirzabaev et al, 2019; Park et al, 2018; Sherwood & Fu, 2014), but this is not supported by recent observations of precipitation (Funk, Harrison, et al, 2019; Orlowsky & Seneviratne, 2013) and other hydrological quantities, including runoff, actual evapotranspiration, and pan evaporation (Roderick & Farquhar, 2002; Scheff, 2018; Ukkola & Prentice, 2013). The previous suggestions of more severe droughts largely arise from uncoupled modeling studies (Sheffield et al, 2012) that do not capture the various climate interactions and generally quantify droughts using potential evapotranspiration in addition to precipitation (Dai, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Many devastating droughts have occurred in recent decades, such as those in California (Griffin & Anchukaitis, 2014), the Horn of Africa (Funk, Shukla, et al, 2019), Europe (Ciais et al, 2005), and Australia (van Dijk et al, 2013), risking regional food and water security. Between 1998 and 2017, droughts are estimated to have impacted 1.5 billion people and accounted for a third of all natural disaster impacts (Funk, Harrison, et al, 2019; United Nations, n.d.). Climate change may be increasing the severity and frequency of droughts (Dai, 2013; Trenberth et al, 2014), posing challenges for water management, agriculture, and natural ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Many devastating droughts have occurred in recent decades, such as those in California (Griffin & Anchukaitis, 2014), the Horn of Africa (Funk, Shukla, et al, 2019), Europe (Ciais et al, 2005), and Australia ( van Dijk et al, 2013), risking regional food and water security. Between 1998 and 2017, droughts are estimated to have impacted 1.5 billion people and accounted for a third of all natural disaster impacts (Funk, Harrison, et al, 2019;United Nations, n.d.). Climate change may be increasing the severity and frequency of droughts (Dai, 2013;Trenberth et al, 2014), posing challenges for water management, agriculture, and natural ecosystems.…”
Section: Introductionmentioning
confidence: 99%